Hyaloterminalis, a novel genus of Coryneaceae in order Diaporthales - Rathnayaka, Achala R.; Wanasinghe, Dhanushka N.; Dayarathne, Monika C.; Chethana, K.w. Thilini; Bhat, D. Jayarama; Kuo, Chang-Hsin; Mortimer, Peter E.; Lumyong, Saisamorn; Hyde, Kevin D. (Phytotaxa, 2020)
The dematiaceous coelomycete Hyaloterminalis alishanensis gen. et sp. nov. (Coryneaceae, Diaporthales, Sordariomycetes) is introduced in this paper. It was isolated from dead branches of Cerasus sp. from the Ali Mountain, Taiwan. Coryneum was previously the only genus in Coryneaceae, and morphological similarity of Hyaloterminalis with the type genus is limited to broadly fusiform, brown conidia. Hyaloterminalis differs from Coryneum in having pycnidial conidiomata, persistent paraphyses and conidiophore morphology, with a long narrow hyaline tip to the apical cell and hyaline basal cells. Multigene phylogenetic analyses, using a combined LSU, ITS and TEF1-α sequence data generated from maximum likelihood, maximum parsimony and MrBayes analyses, confirmed that Hyaloterminalis forms a distinct lineage within Coryneaceae and its establishment as a new genus is well-supported. The new taxon is described, illustrated and compared with Coryneum. The ITS (MH861215) and LSU (MH872982) sequences obtained from the ex-type strain of Talekpea foeticia, confirm its status as a member in Coryneaceae. Therefore, Talekpea is accepted as a distinct genus in Coryneaceae.